Reconstrucción 3D de objetos sumergidos en aguas limpias - Muñoz Robles, Leydy Viviana; Quiñónez Jiménez, Edilson; Pizo, Héctor Daniel Victoria (Ingeniería, 2013)
This paper presents the development of a hardware / software system that allows reconstructing objects immersed in water and provides the possibility that the results can be seen from different perspectives in a virtual environment. Describes how from projecting a laser line on the object, it is possible to extract the spatial coordinates (x, y, z) of each projected point by using the triangulation technique. Within the document describes the steps taken to obtain the three-dimensional model of an isometric view of the object, which begin with scanning of the object, passing through the capture, processing and image processing, and ending with the calculation of the coordinates space, obtaining and rendering point cloud. Preliminary results with a variety of common objects are described.